Fermentation of biodiesel-derived waste for 1,3-propanediol production with response surface methodology - Stasha Eleanor Rosland Abel (2020)
The present study aimed to investigate the fermentation conditions favouring the maximum production of 1,3-propanediol (1,3-PD) from crude glycerol. Response surface methodology (RSM) based on central composite design (CCD) was applied in designing the experiments to evaluate the interactive effects of glycerol concentration (20 to 50 g litre-1), pH (6 to 8), temperature (30°C to 40°C) and incubation time (48 to 72 hr) on 1,3-PD production. A total of 30 experimental runs consisting of 16 factorial points, eight axial points and six centre points were conducted. It was found that the derived optimum conditions were: 39.9 g litre-1 glycerol; pH: 7.6, temperature: 33°C and incubation time: 59.1 hr. Under these conditions, the 1,3-PD produced (9.85 g litre-1) was ~2% higher than the predicted value by RSM (9.69 g litre-1), hence, the experimental design employed in validating the results obtained was significant. The analysis of variance (ANOVA) showed high coefficient of the determination values (R2) of 0.9444. The fermentation using RSM was able to increase the 1,3-PD production by two-fold.